3a+18分之a的平方+3a-18化简.
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 10:54:51
3a+18分之a的平方+3a-18化简.3a+18分之a的平方+3a-18化简.3a+18分之a的平方+3a-18化简.3a+18分之a的平方+3a-18=3(a+6)分之(a-3)(a+6)=3分之
3a+18分之a的平方+3a-18化简.
3a+18分之a的平方+3a-18化简.
3a+18分之a的平方+3a-18化简.
3a+18分之a的平方+3a-18
=3(a+6)分之(a-3)(a+6)
=3分之(a-3)
化简:a的平方+6a+9分之a的平方/a的平方+3a分之a-3-a-1分之a-a的平方
化简:a的平方-1分之a的平方+3 - a-1分之a+1=
(a-1分之2)-(a的平方+8a-9分之a+2)÷(2a+18分之3)
3a+18分之a的平方+3a-18化简.
(a-3分之a的平方+3-a分之a)除以a分之a+3
a的平方-4a+3分之a的平方-3a+2(化简)
化简:a的平方-7a+12分之a的平方-2a-3
a+1分之1+a的平方-2a-3分之a的平方-a除以a-3分之a
化简a的平方+a分之a
已知a的平方-3a+1=0,求a+a分之1、a的平方+a的平方分之1、(a-a分之1)平方
计算:2分之1√8a的立方+6a√18分之a-3a的平方√a分之2(a>0)
a+3分之a的平方/a的平方-9分之6a
若a+a分之1=3,求a平方+a平方分之1的值
已知a+a分之1=3则a的平方+a平方分之1
3a-12a的平方+18a的平方
化简:(a的平方-1)分之a的平方+3)-(a-1)分之(a+1)+1=
a+3分之1-9-a平方分之6,1-(a-1-a分之1)÷a平方-2a+1分之a平方-a+1计算.a-1分之a÷a平方-1分之a平方-1-a-1分之1计算,化简(a平方-ab分之b+b平方-ab分之a)×a+b分之ab
a+3分之1-9-a平方分之6,1-(a-1-a分之1)÷a平方-2a+1分之a平方-a+1计算.a-1分之a÷a平方-1分之a平方-1-a-1分之1计算,化简(a平方-ab分之b+b平方-ab分之a)×a+b分之ab